2004
DOI: 10.1111/j.0953-816x.2004.03291.x
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line‐derived neurotrophic factor (GDNF) from adult rat tooth serves a distinct population of large‐sized trigeminal neurons

Abstract: Glial cell line-derived neurotrophic factor (GDNF) mediates trophic effects for specific classes of sensory neurons. The adult tooth pulp is a well-defined target of sensory trigeminal innervation. Here we investigated potential roles of GDNF in the regulation of adult trigeminal neurons and the dental pulp nerve supply of the rat maxillary first molar. Western blot analysis and radioactive 35S-UTP in situ hybridization revealed that GDNF in the dental pulp and its mRNAs were localized with Ngf in the coronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 70 publications
5
20
0
3
Order By: Relevance
“…Using this approach, we found that pulpal afferents were 2.5% GFPpositive in mice. This confirms the results from the studies in rats reporting a rare population of IB4-positive pulpal afferents identified by approaches similar to those used in the current study (Fried et al, 1989;Yang et al, 2002;Kvinnsland et al, 2004;Gibbs et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using this approach, we found that pulpal afferents were 2.5% GFPpositive in mice. This confirms the results from the studies in rats reporting a rare population of IB4-positive pulpal afferents identified by approaches similar to those used in the current study (Fried et al, 1989;Yang et al, 2002;Kvinnsland et al, 2004;Gibbs et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…The extent of the proportion of IB4-positive pulpal afferents in retrogradely labeled pulpal afferents is controversial. In rats, labeling of IB4 in TG sections showed that less than 5% of retrogradely labeled dental afferents are IB4-positive (Fried et al, 1989;Yang et al, 2002;Kvinnsland et al, 2004;Gibbs et al, 2011). In contrast, the percentages of IB4-positive pulpal afferents in cultured dental afferents were as high as 75% (Park et al, 2006;Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our tissue recombination experiments showing that the E10.5 oral and E11 dental epithelia induce mesenchymal Sema3a expression indicate that, besides the odontogenic information, the presumptive dental epithelium also possesses the instructive information to control the formation of early tooth nerve supply and possible tooth-specific sensory innervation that is distinct, in some aspects, from the adjacent cutaneous sensory system (Fried et al, 2000;Kvinnsland et al, 2004). Furthermore, because the formation of teeth of all types is controlled by the epithelialmesenchymal interactions, the interactions also appear to provide a rationale for the fact that the timing and pattern of tooth innervation in different teeth and species correlate better to the developmental stage of the individual tooth than the chronological age of the animal.…”
Section: Epithelial-mesenchymal Interactions Regulate the Establishmementioning
confidence: 90%
“…Among these, nerve growth factor is a candidate for directing early pulp innervation in both incisors and molars because mice with a knockout of the trkA nerve growth factor receptor lack sensory nerves in the pulp of molars and incisors (Matsuo et al ., 2001). Glial cell line‐derived neurotrophic factor has also been shown to participate in dental pulp innervation (Luukko et al ., 1997; Kvinnsland et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%